Probability and statistics - Freudenthal, Hans (Amsterdam Elsevier publishing co., 1965)
Probability and statistics are two interconnected fields in mathematics. Probability deals with the likelihood of events, while statistics focuses on collecting, analyzing, interpreting, and presenting data. Essentially, probability helps us understand the chances of something happening, while statistics helps us make sense of data and draw conclusions.
Keywords: Probability theory; Statistics theory; Mathematics